Komitmen Organisasional Memediasi Pengaruh Kompetensi Dan Counterproductive Work Behavior Terhadap Kinerja - Prof. Dr. Yupono Bagyo, MM, MS, CHRP, CPTM; Rifatul Khusnia (Fakultas Ekonomi Universitas Kadiri, 2021)
This study aims to determine whether there is an effect of competence on organizational commitment, competence on performance the influence of competence on performance through organizational commitment, the influence of the CWB on organizational commitment, CWB on performance, the influence of organizational commitment on employee performance and the influence of CWB on performance through organizational commitment. With the help of literature, the current study developed seven hypotheses regarding competence, counterproductive work behavior (CWB), organizational commitment, and performance. The distribution of questionnaires was used for data collection carried out at the Pasuruan City Regional Revenue Agency and the Pasuruan City Financial and Asset Management Agency with a population of 59 employees and a sample of 50 employees. Using Partial Least Square as a data analysis method, the results showed that competence has no significant effect on organizational commitment, competence has a significant effect on performance, competence indirectly through organizational commitment as an intervening variable has no significant effect on performance, CWB has a significant effect on organizational commitment, CWB has a significant effect on performance, organizational commitment has a significant effect on performance, and CWB indirectly through organizational commitment as an intervening variable has a significant effect on performance.